2019
DOI: 10.1002/nme.6211
|View full text |Cite
|
Sign up to set email alerts
|

A simultaneous approach for compliance minimization and piezoelectric actuator design considering the polarization profile

Abstract: Summary This article addresses the compliance problem along with the piezoelectric actuator design for active vibration control. The topology structural design is obtained by solving a compliance minimization problem with volume constraint, whereas the actuator design is carried out by the maximization of a control performance index written in terms of the controllability Gramian. This measure describes the ability of the actuator to move the structure from an initial condition to a desired final state, at res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Lucinskis et al (2018) investigated two-dimensional polarised actuators experimentally with prototyped beams. Others have considered multioptimisation of the polarisation profile and structure of piezoelectric devices (Gonçalves et al 2020, Homayouni-Amlashi et al 2020a, 2020b. Homayouni-Amlashi et al (2020a) showed that multi-poled energy harvesters could be used to harvest energy that comes from excitation in different directions.…”
Section: Introductionmentioning
confidence: 99%
“…Lucinskis et al (2018) investigated two-dimensional polarised actuators experimentally with prototyped beams. Others have considered multioptimisation of the polarisation profile and structure of piezoelectric devices (Gonçalves et al 2020, Homayouni-Amlashi et al 2020a, 2020b. Homayouni-Amlashi et al (2020a) showed that multi-poled energy harvesters could be used to harvest energy that comes from excitation in different directions.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the PEMAP-P model has been applied in different design problems. [25][26][27][28][29] The simultaneous optimization of control systems along with the structure has been grown in importance with the development of new materials. Hać and Liu, 30 proposed a measure based on the controllability Gramian matrix to maximize the performance of a control system.…”
Section: Introductionmentioning
confidence: 99%